Calcaneal bone mineral and ultrasound attenuation in male athletes exposed to weight-bearing and nonweight-bearing activity. A cross-sectional report - Taaffe, D. R.; Suominen, H.; Ollikainen, S.; Cheng, S. (The Journal of Sports Medicine and Physical Fitness, 2001)
To determine if the expected differences in bone mineral content/density of the calcaneus among male athletic groups that undertake weight-bearing and nonweight-bearing activity are also apparent for bone quality as assessed by quantitative ultrasound (QUS) attenuation. METHODS: Experimental design: cross-sectional. Setting: a University research laboratory. Participants: we studied 30 young men: 10 Finnish national level jumpers whose training incorporates repeated impacts to the heel, 10 aquatics athletes whose skeletons are exposed to nonweight-bearing activity, and 10 sedentary men matched for age and body weight. Measures: bone mineral content (BMC, g.cm-1), areal bone mineral density (BMDa; g.cm-2) and presumed volumetric BMD (BMDv, g.cm-3) was measured by single energy photon absorption (SPA). Broadband ultrasound attenuation (BUA using Fourier spectral estimation and UBI-4 using Burg spectral estimation, both in db/MHz) was assessed by a new QUS device (QUS-1TM, Metra Biosystems). RESULTS: There was no difference in years of sport specific training or total training time per week between athlete groups. BMC, BMDa and BMDv were significantly different among groups (p=0.0001) with jumpers being higher than aquatics athletes and controls. BMC of jumpers was 52% and 39% higher than controls and aquatics athletes, respectively, while the corresponding values for BMDv were 34% and 28%. However, BUA values were not significantly different (p=0.10) among groups nor was UBI-4 (p=0.03; jumpers values were 7% and 6% higher than aquatics athletes and controls, respectively). CONCLUSIONS: These cross-sectional results indicate that bone mineral content and density of the calcaneus are substantially higher in jumpers than individuals engaged in nonweight-bearing or regular weight-bearing activity. However, parameters assessed by QUS attenuation are not markedly different, which suggests that bone quality properties may not be as responsive as that of bone mineral content/density to habitual skeletal loading.